Albert Camus, um resistente político - Jesus, Tânia Elias de (2013)
The research had the purpose of making a profound study and a proper comprehension of the Camusian works, especially concerning the aesthetical-political-philosophical question. From Albert Camus philosophy, we attempted to find the conditions to think of the aesthetical field as a possibility of resistance and consciousness of The Man In Revolt . We don t intend to say that this consciousness was not subsumed to the historicity of Art, but, before that, we believe that it denotes resistance qualities, political consciousness, featuring the particularities of the construction of an independent Thought, capable of creating with the purpose of resisting. To justify this search, it was proposed to show the importance of the Camusian concepts Happiness, Absurd and Revolt which are primordial on the structure of his Thought. These concepts are the guiding principle of his philosophy, as well as the connectors between the questions. Furthermore, through the study, we observed how determinant was the nihilism for the transformation of Revolt, and how it contributed for the introduction of Totalitarianism, that, in its turn, in Camus views, brought about the terror and terrorism practices.